Production and regulation of lignocellulose-degrading enzymes of Poria-like wood-inhabiting basidiomycetes - Tomsovský, M; Popelárová, P; Baldrian, P (Folia microbiologica, 2009)
The wood-decomposing fungal species Antrodia macra, A. pulvinascens, Ceriporiopsis aneirina, C. resinascens and Dichomitus albidofuscus were determined for production of laccase (LAC), Mn peroxidase (MnP), lignin peroxidase (LiP), endo-l,4-P-beta-glucanase, endo-l,4-beta-xylanase, cellobiohydrolase, 1,4-beta-glucosidase and 1,4-beta-xylosidase. The results confirmed the brown-rot mode of Antrodia spp. which did not produce the activity of LAC and MnP. The remaining species performed detectable activity of both enzymes while no strain produced LiP. Significant inhibition of LAC production by high nitrogen was found in all white-rot species while only MnP of D. albidofuscus was regulated in the same way. The endoglucanase and endoxylanase activities of white-rotting species were inhibited by glucose in the medium while those of Antrodia spp. were not influenced by glucose concentration. The regulation of enzyme activity and bio-mass production can vary even within a single fungal genus.
Keywords: Laccase; dusík; Nitrogen; Fungal Proteins; Basidiomycota; lignin; peroxidasy; Peroxidases; fungální proteiny; Wood; Lignin; lakasa; dřevo